Gendered Social Capital - A Case Study of Sports and Music Associations in Leksand and Rättvik, Sweden - Karin Tillberg Mattsson; Susanne Stenbacka (European Regional Science Association (ERSA), 2003)
Earlier research has been able to establish a connection on an aggregated level between a lively participation in voluntary organisations and a flourishing economy. This has been explained in terms of dense, informal networks of civic engagement fostering norms of reciprocity and trust - i.e. social capital - which in turn facilitate co-operation and successful economic development. The causality on the individual level, that is the relationship between engagement in the voluntary sector and position on the labour market, has been less studied, though. In this paper, we focus on various qualities which the links between an individual's participation in the voluntary sector and position on the labour market/local business can have. We concentrate on gender aspects. The empirical findings originate from a study of two rural municipalities, Leksand and Rättvik, located in the region of Dalarna in Sweden. The area is characterised by a high degree of civic engagement in voluntary organisations. The study focuses on sports and cultural associations and illuminates the different kinds of voluntary engagement in these, especially the differences between female and male actors. Preliminary results show that there are gender differences concerning the degree to which the informal networks related to a voluntary organisation reach from this over to other local sectors. Men to a higher degree than women are members of "cross-sectional" networks linking the voluntary sector with others, like the business, politics and municipal authority. One example of such a male-dominated, possibly excluding network is the one linking the sectors of business and municipal authority via the association of ice-hockey in Leksand. On the individual level, the men seem to have a more direct connection between their participation in a voluntary organisation and their paid job. For example, they might use the contacts they get through their voluntary engagement in their private business. On the other hand, their position on the labour market/business sector may have led to them being offered the current (high) position in the voluntary organisation. Men to a higher degree than women hold positions in committee boards in large, semi-commercial sports and cultural associations. For the women, such a direct link between their voluntary engagement and their paid job seems less common. They hold hierarchically lower positions in the associations than men, and in cases where they are members of committee boards, this is more typically in smaller, non-commercial associations. This also means that women are less likely to be members of networks stretching from the voluntary sector to other societal sectors, like business or the municipal authority. Earlier research has pointed to a relationship between informal networks related to the voluntary sector and the development of a community. Our study points to gender differences regarding the degree to which these networks are cross-sectional. Such differences may be assumed to lead to gender inequalities regarding the power to influence the officially promoted line of development. Key words: social capital, networks, gender, exclusion, Leksand-Rättvik, Sweden
Keywords: 330